If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(y + 6) + -3y + -1 = 0 Reorder the terms: 8(6 + y) + -3y + -1 = 0 (6 * 8 + y * 8) + -3y + -1 = 0 (48 + 8y) + -3y + -1 = 0 Reorder the terms: 48 + -1 + 8y + -3y = 0 Combine like terms: 48 + -1 = 47 47 + 8y + -3y = 0 Combine like terms: 8y + -3y = 5y 47 + 5y = 0 Solving 47 + 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + -47 + 5y = 0 + -47 Combine like terms: 47 + -47 = 0 0 + 5y = 0 + -47 5y = 0 + -47 Combine like terms: 0 + -47 = -47 5y = -47 Divide each side by '5'. y = -9.4 Simplifying y = -9.4
| 5y-7=7y-9 | | -3c+(-2)=-8 | | 18p-45=3 | | -15-3v-3v=-6-4v-1 | | 3x^2-33x+48=0 | | 12=x(10-2x) | | 25=5(5x+1) | | y=-3-2+5 | | -0.848=-0.2(6.5-2) | | 2.7t^2-13t+5=3 | | 2(4x-2)-2x=0.5x-0.5 | | .125y-10=20 | | 2(4x-2)-2x=2x-3 | | 2(4x-2)-2x=1x-1 | | -3(x+2)+5=5(x+5)+5 | | 15=5-(y+8) | | -6-7+2x-8=2x+7x | | 6y+10=8y | | 2y+7x=2 | | 2(4x-2)-1.5x=1.5x-2 | | -20+x=-12 | | x+9.031=0.348 | | .6w-.5w+.4w=4 | | 2.4x^2+4.2x+1.2=0 | | 3000=(15-.50x)(200+8x) | | 2(4x-2)-2x=2x-2 | | 4y+3=7y | | y=-3-4+5 | | 4h-2h+3=2h+2h | | -9x+x^2=-9 | | -7m+3=31 | | 0.3x-0.5(3-x)=1.3 |